Analisis Matagenom Komunitas Bakteri Tempe dengan Teknik Terminal Restriction Fragment Length Polymorphism (T-RFLP) - Tati Barus; Griselda Griselda; Antonius Suwanto; Tan Watumesa Agustina (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2010)
Bacteria have an important role in tempe fermentation in Indonesia, aside of Rhizopus oligosporus as the dominant microbe. In this study the molecular aspect of bacterial diversity in tempe were analyzed using a fingerprinting technique, Terminal-Restriction Fragment Length Polymorphism (T-RFLP). This study was aimed to examine the diversity of bacterial community during tempe making. Bacterial diversity analysis was conducted in the first hour and the thirteenth hour after the soybean soaked while the fresh tempe was analysed at one to two hours after the fermentation ended. T-RFLP can be used to describe the diversity of bacterial community during the fermentation of tempe. T-RFLP profiles revealed the presence of 24, 30 and 33 bacterial phylotypes in the first hour and the thirteenth hour after the soybean soaked as well as in fresh tempe samples. The phylotypes were dominated by unculturable bacteria group. Only several bacterial phylotypes were consistenly identified since the beginning to the end of fermentation, while most of them were only identified at certain phases along with the environmental changes (i.e: pH) that occured during the fermentation process. One of the consistently identified groups belongs to Bacillus genera.